Control the Sensitivity of the Encryption Key to Ensure the Security of Big Data - Wafaa Ali; Alajali, Walaa; Abdulrahman D. Alhusaynat (The Indonesian Journal of Computer Science, 2025)
With the increasing technological development that has led to the complexity of big data systems, the importance lies in the challenge that ensures the security of sensitive information. Encryption is one of the basic methods used to protect data, hence the importance of the encryption key and its sensitivity, which play a vital role in the strength of encryption. Encryption sensitivity is the simple change in the encryption key that produces a very different encrypted text. This study is concerned with methods of controlling the sensitivity of the encryption key and its effect on the strength of encryption of big data. This context is in line with the nature of cloud data and the focus on the attacks that this data suffers from, such as brute-force attacks and statistical attacks. The research discusses the components that make up the encryption key, logistics maps, and chaos. The results reached by the study proved the merit of the research in terms of accuracy 1015 and appropriate key sensitivity 2128. This study discussed future challenges and the possibility of using artificial intelligence algorithms and adaptive security algorithms and solving quantum encryption problems.